The Spatial Data Analysis of Determinants of U.S. Presidential Voting Results in the Rustbelt States during the COVID-19 Pandemic - Shianghau Wu (ISPRS International Journal of Geo-Information, 2023)
This study aims to analyze the factors that determine voting behavior in the rustbelt states during the 2020 U.S. presidential election. The rustbelt states are traditionally considered “swing states” and play a crucial role in determining the outcome of the presidential election. The study employs a spatial econometrics model that considers COVID-19-related factors, such as the percentage of people wearing masks and the number of COVID-19 deaths in each county of the rustbelt states. Firstly, the study identifies the most suitable spatial econometrics model. Secondly, the study shows that COVID-19 pandemic-related independent variables had a significant positive impact on the Republican Party’s results in the U.S. presidential election while mask-wearing behavior had a significant negative impact. These results suggest that the COVID-19 pandemic has influenced voting behavior and altered the political landscape, but it does not have geographical effects.